(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Cancer is currently a major public health problem worldwide. Approximately 20 per cent of people (up to the age of 75) develop cancer in their lifetime and 10 per cent of people worldwide die. In 2020, the number of cancer cases reached 19.3 million and nearly 10.0 cancer deaths. Breast cancer is the most frequently diagnosed cancer in women worldwide (2.26 million cases). In this article, we conducted a bibliometric analysis of 550 articles with the keywords "checkpoint kinase 2" and "breast cancer." The source of the articles was the Scopus database, and bibliometric laws were utilized to determine the growth trends in publications from 2018 to 2022, the most cited and prolific authors, as well as the articles and journals in this scientific field. An analysis of countries, organizations, publications, and keywords most frequently used by authors was also carried out. The study reveals an exponential trend in the number of publications on breast cancer and the CHEK2 gen.